Resistance exercise increases postexercise oxygen consumption in nonexercising muscle - Nagasawa, Takeshi (European journal of applied physiology, 2008)
This study examined the effect of knee extension resistance exercise on muscle oxygen consumption in nonexercising forearm flexor muscles after exercise. Seven healthy male subjects were performed six sets of unilateral knee extension exercise until exhaustion at 40, 60, and 80% of 1 repetition maximum (RM) on separate days. The values at rest, at the end of exercise, and during recovery after exercise were measured by near-infrared spectroscopy. The at the end of exercise was significantly ( P < 0.05) increased by 1.8 ± 0.2, 1.7 ± 0.2, and 1.4 ± 0.3 fold over resting value at 40, 60 and 80% 1RM, respectively. returned to the resting values after 1–5 min of recovery and then showed no further significant change for all exercise intensities. This study suggests that knee extension resistance exercise at 40, 60 and 80% 1RM induced an increase in and that the increase of after exercise returned to resting value in several minutes.